2020
DOI: 10.3390/ijms21114014
|View full text |Cite
|
Sign up to set email alerts
|

Ionising Radiation Induces Promoter DNA Hypomethylation and Perturbs Transcriptional Activity of Genes Involved in Morphogenesis during Gastrulation in Zebrafish

Abstract: Embryonic development is particularly vulnerable to stress and DNA damage, as mutations can accumulate through cell proliferation in a wide number of cells and organs. However, the biological effects of chronic exposure to ionising radiation (IR) at low and moderate dose rates (< 6 mGy/h) remain largely controversial, raising concerns for environmental protection. The present study focuses on the molecular effects of IR (0.005 to 50 mGy/h) on zebrafish embryos at the gastrula stage (6 hpf), at both the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The changes in gene expression observed in the CEZ are thus not solely a consequence of genetic differentiation inside the CEZ but rather the result of ITDR differences, despite other environmental characteristics specific to the CEZ cannot be completely excluded. Furthermore, the biological effects detected by the transcriptomic analysis, collectively point toward deregulations of mitochondrial activity and muscle functions in frogs living in the CEZ, which fits with the known effects of chronic exposures to IR [ 62 65 ].…”
Section: Discussionmentioning
confidence: 62%
“…The changes in gene expression observed in the CEZ are thus not solely a consequence of genetic differentiation inside the CEZ but rather the result of ITDR differences, despite other environmental characteristics specific to the CEZ cannot be completely excluded. Furthermore, the biological effects detected by the transcriptomic analysis, collectively point toward deregulations of mitochondrial activity and muscle functions in frogs living in the CEZ, which fits with the known effects of chronic exposures to IR [ 62 65 ].…”
Section: Discussionmentioning
confidence: 62%
“…Genes with |fold change| ≥ 1.5 and p -value corrected for multiple testing, fdr < 0.05 (false discovery rate [ 63 ]) were considered as differentially expressed in all analysis. Afterwards, functional enrichments was performed using Gene ontology (GO) with R package clusterProfiler using zebrafish genes and human orthologues retrieved by Ensembl biomart (as published before, [ 64 , 65 , 66 ]) as gene annotation is more abundant in this species. The significance was considered when fdr from Fisher’s exact test was <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been shown that radiation can lead to hypomethylation of DNA, as demonstrated by hepatic methionine depletion in rodent models. 15,[46][47][48] Thereby, radiation-induced aberrant methylation activity may be partly responsible for elevated PE, LPE, and reduced PC levels. Furthermore, the decreased levels of plasma PC could be related to their rapid turnover in stressed or damaged cells, which resulted in increased uptake of PC from the blood.…”
Section: Lipid Metabolismmentioning
confidence: 99%